Minocycline synergizes with corticosteroids in reducing colitis severity in mice via the modulation of pro-inflammatory molecules - Khajah, Maitham A.; Hawai, Sanaa; Barakat, Ahmad; Albaloushi, Aisha; Alkharji, Maha; Masocha, Willias (Frontiers in Pharmacology, 2023)
Background: A few studies have highlighted the anti-inflammatory properties of minocycline in reducing colitis severity in mice, but its molecular mechanism is not fully understood. The aim of this study was to determine the anti-inflammatory properties of minocycline and the expression/activity profile of molecules involved in the proinflammatory signaling cascades, cytokines, and molecules involved in the apoptotic machinery. The synergistic effect between minocycline and corticosteroids was also evaluated. Methods: The effects of various treatment approaches were determined in mice using the dextran sulfate sodium (DSS) colitis model at gross and microscopic levels. The expression/activity profile of various pro-or anti-inflammatory molecules was determined by western blotting and polymerase chain reaction (PCR). Results: Minocycline treatment significantly reduced colitis severity using prophylactic and treatment approaches and produced a synergistic effect with budesonide and methylprednisolone in reducing the active state of colitis. This was mediated in part through reduced colonic expression/activity of proinflammatory molecules, cytokines, proteins involved in the apoptotic machinery, and increased expression of the antiinflammatory cytokine IL-10. Conclusion: Minocycline synergizes with corticosteroids to reduce colitis severity, which could reduce their dose-dependent side effects and treatment cost. The reduction in colitis severity was achieved through modulating the expression/activity profile of various pro-and anti-inflammatory signaling molecules and cytokines, and molecules involved in the apoptotic machinery